Beef on dairy economic selection index - Kilian, Levi, author; Enns, Richard Mark, advisor; Speidel, Scott, advisor; Ritten, John, committee member (Colorado State University. Libraries, 2025)
The objective of this study was to create an economic selection index for a beef on dairy crossbreeding system. In an effort to improve overall performance in the system, the index aims to increase profitability. Crossbreeding a beef bull with a dairy female aims to add value to the resulting calf entering the beef supply chain. Historically, dairy animals entering the beef supply chain have mostly been in the form of veal production as diary animals lack the growth and carcass performance characteristics of a beef animal. Data from previous literature as well as some current industry was used to derive a profit equation. The economic values used in the economic selection index were derived using the profit equation. The resulting economic selection index when compared to iGENDEC had a higher response to selection for efficiency traits largely due to the inclusion of average daily gain (ADG). The presented index also showed a positive response to selection for carcass weight (86.07 kg), ribeye area (9.78 sq. cm), and marbling (1.29). The economic index derived in this study can be used to improve the profitability of beef on diary production systems, due to these positive responses to selection.
Keywords: bovine; selection index; economic selection index; beef on dairy